The Political Economy of International Financial Institutions? Lending to Pakistan - Mumtaz Anwar (Hamburg Institute of International Economics (HWWA), 2005)
This paper analyzes the determinants of international financial institutions (IFIs)'s lending decisions to Pakistan. At the example of three major IFIs, the World Bank, IMF and ADB, this paper suggests that political economic factors, notably bureaucratic interest of international civil servants and major shareholders' economic interest belong to the most relevant determinants of international lending. Pooled Tobit estimation analysis for the period ever since when these institutions established their lending instruments to developing countries, confirm this hypothesis. Recipients' need is shown to have some relevance as well but not as strong as bureaucratic interest. Further analysis suggests that IDA and ADB lending is more interest oriented than lending by the IBRD and IMF.
Keywords: F35; D70; 330; Foreign aid; International organizations; bureaucracy; Internationale Kreditvergabe; Interessenpolitik; Public Choice; Ausländisch; Pakistan